Nrf2 expression is increased in peripheral blood mononuclear cells derived from mild–moderate ex-smoker COPD patients with persistent oxidative stress - Fratta Pasini, Anna Maria (Int J Chron Obstruct Pulmon Dis, 2016)
Inadequacy of antioxidant nuclear factor-E2-related factor 2 (Nrf2) and endoplasmic reticulum stress-mediated unfolded protein response has been implicated in severe chronic obstructive pulmonary disease (COPD) and cigarette smoking-induced emphysema. As evidence suggests that the ability to upregulate Nrf2 expression may influence the progression of COPD and no data exist up to now in ex-smokers with mild–moderate COPD, this study was first aimed to evaluate Nrf2 and unfolded protein response expression in peripheral blood mononuclear cells (PBMC) of mild–moderate ex-smokers with COPD compared to smoking habit-matched non-COPD subjects. Then, we tested whether oxidative stress persists after cigarette smoking cessation and whether the concentrations of oxidized phospholipids (oxidation products of the phospholipid 1-palmitoyl-2-arachidonyl-sn-glycero-3-phosphorylcholine [oxPAPC]) in the PBMC of the same subjects may have a causative role in determining the upregulation of Nrf2. The expression (mRNA and protein) of Nrf2 and of its related gene heme oxygenase-1 was significantly increased in COPD group without differences in the unfolded protein response. Plasma malondialdehyde, the circulating marker of oxidative stress, and oxPAPC in PBMC were significantly higher in COPD than in non-COPD subjects. The fact that the expression of p47phox, a subunit of NADPH oxidase, was increased in PBMC of COPD patients and that it was directly correlated with oxPAPC may indicate that oxPAPC may be one of the determinants of oxidative stress-induced Nrf2 upregulation. Finally, we also demonstrated that lung function inversely correlated with plasma malondialdehyde and with Nrf2 and heme oxygenase-1 mRNA expression in all subjects. Our results indicate that mild–moderate ex-smokers with COPD may be able to counteract oxidative stress by increasing the expression of Nrf2/antioxidant-response elements. Because Nrf2 failure significantly contributes to the development of COPD, our findings suggest that the possibility to prevent Nrf2 reduction may open a new scenario in helping to prevent the oxidative stress-associated lung function decline.